Dyke Award. Evaluation of contrast-enhanced MR imaging in a brain-abscess model. - Runge, V M; Clanton, J A; Price, A C; Herzer, W A; Allen, J H; Partain, C L; James, A E (American Journal of Neuroradiology, 1985)
An alpha-streptococcus brain abscess was produced in five dogs and studied with magnetic resonance (MR) imaging (0.5 T) and computed tomography (CT). Non-contrast- and contrast-enhanced CT scans were obtained using gadolinium diethylenetriamine-pentaacetic acid (Gd DTPA) for MR imaging and meglumine iothalamate for CT scanning. Each animal was evaluated in the early and later cerebritis stages of abscess evolution. On MR, the area of cerebritis enhanced after administration of Gd DTPA in a manner similar to that observed with contrast-enhanced CT. However, contrast enhancement was greater on the MR examination. Early lesions in two animals were detected only with contrast-enhanced MR imaging. This experience suggests that intravenously administered agents such as Gd DTPA should increase the diagnostic potential of MR imaging in neurologic diseases, especially those altering the blood-brain barrier.